Exploration Of Sustainability Models In City Branding: Integration Of Local Culture, Digital Media, And Multisector Collaboration - Lestari, Evi; Nurhidayati, Safitri; Yuliani, Marifah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to develop a substantive theory of sustainable city branding in small cities, with a focus on Berau. Using a qualitative approach grounded in Grounded Theory, data were collected through interviews, observations, and document analysis, then analyzed iteratively to identify key processes and relationships. The findings reveal that successful city branding relies not only on natural potential and leadership support but also on complex interactions among multisector collaboration, active community participation, and strategic digital media use. The theory emphasizes that sustainability in this context involves holistic integration of local culture, environmental concerns, and economic development through concrete, collaborative steps. This model highlights the importance of active stakeholder engagement and innovative digital strategies in building an authentic and sustainable city image. The study contributes to understanding how small cities can effectively implement sustainable branding practices through a process of collective effort and strategic management.